Corporate governance within the holding entities: specifics and instruments - Yushko, Kseniya (Journal of the Belarusian State University. Economics, 2018)
The article covers the specifics of the corporate governance within the holding entities. The article also covers the substance of the execution of the governance system through the representatives of the management board of the subsidiaries and the possibilities of its practical applications through the instruments of the corporate governance within the governance system of the holding entity. The article provides the latest and most modern global recommendations in the respect of the corporate governance in the holding entities, which are recommended from such international institutions as International Financial Corporation, Banking Supervision of Basel Committee. There is also an analysis of the models of the Corporate Center, the role of the parent company as well as the levels of its interference in the operations of the subsidiaries. The author has compiled the key differences of corporate governance practices in the Belarussian holding entities from the respective best international standards.